FluidRegNet: Longitudinal registration of retinal OCT images with new pathological fluids - Andresen, Julia; Jan Ehrhardt; von der Burchard, Claus; Tatli, Ayse; Roider, Johann; Heinz Handels; Uzunova, Hristina (Proceedings of The 7nd International Conference on Medical Imaging with Deep Learning, 2024)
Eye diseases such as the chronic central serous chorioretinopathy are characterized by fluid deposits that alter the retina and impair vision. These fluids occur at irregular intervals and may dissolve spontaneously or thanks to treatment. Accurately capturing this behavior within an image registration framework is challenging due to the resulting prominent tissue deformations and missing image correspondences between visits. This paper presents FluidRegNet, a convolutional neural network for the registration of successive optical coherence tomography images of the retina. The correspondence between time points is established by predicting the position of the origin of the fluids by creating a fluid seed in the form of sparse intensity offsets in the moving image and registering the fluid seed to the affected area in the follow-up image. We show that this leads to deformation fields that more accurately reflect the actual dynamics of retinal fluid growth compared to other image registration methods. In addition, the network outputs are used for unsupervised fluid segmentation.